Relations Along, not Between: Incorporating Becoming into Relational Sociology (via Life-Philosophy) - Pyyhtinen, Olli (Simmel Studies)

(untitled) (Edizioni ETS, 2021)
The article advances a type of relational sociology that is sensitive to the continually ongoing formation of beings and relations over the course of time. While the dynamic and fluid character of relations has been stressed by other relational scholars as well, the article suggests by drawing from the work of Simmel and anthropologist Tim Ingold that to attend to the coming-into-being and change of beings and relations, we need to alter the very grammar of considering relations: instead of fathoming them as connections between entities, we had better examine them as lines of life along which things become, act, change, move, and grow. This is to interweave the concept of relations with the notion of life, which the article conceptualizes by turning to the life-philosophy of Simmel. Instead of regarding life as encapsulated inside living organisms, Simmel considers it as form-giving immanent in the world’s incessant processes of becoming.